For the Sake of All: Civic Education on the Social Determinants of Health and Health Disparities in St. Louis. (July 2018) - Purnell, Jason Q.; Goodman, Melody; Tate, William F.; Harris, Kelly M.; Hudson, Darrell L.; Jones, Brittni D.; Fields, Robert; Camberos, Gabriela; Elder, Keith; Drake, Bettina; Gilbert, Keon
Civic education translates research evidence about topics of social importance for broad public audiences, with increased understanding and meaningful action of the desired outcomes. For the Sake of All is an example of civic education on the social determinants of health and health disparities situated in the local context of St. Louis, Missouri. This article describes the research translation, community engagement, strategic communication, and approach to policy that characterized this project. It presents data highlighting racial disparities in health, educational, and economic outcomes, along with policy and programmatic recommendations. Engagement and implementation strategies are described within the context of the events in Ferguson.